2022
DOI: 10.1097/iae.0000000000003371
|View full text |Cite
|
Sign up to set email alerts
|

Myths and Truths of the Association of Retinal Vascular Occlusion With Covid-19

Abstract: Purpose: To critically review data published in the recent past to scrutinize a causal relationship between retinal vascular occlusion and COVID-19.Method: A comprehensive literature search was performed on Pubmed with the key words retinal vascular occlusion, retinal vein occlusion, retinal artery occlusion, and COVID-19.Results: A total of 17 case reports were published during this period, and 10 were on retinal vein occlusion and 7 on retinal artery occlusion. Most of the published reports lacked convincing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Baseline BCVA was the only significant predictor for BCVA changes among previously treated subjects in a multivariable regression analysis. Several recent studies have stated that most of the missing followup visits in the COVID19 period belonged to the elderly popula tion [28,29]; however, we showed no significant age dif ference between 2020 and 2019. Better baseline BCVA is a known predictor for final BCVA, and in a lower baseline BCVA, a bigger improvement can be achieved [11,30], and we showed among study cohorts that any previous BCVA, within the second year of treatment forward, is a significant BCVA predictor for the following year.…”
Section: Discussioncontrasting
confidence: 83%
“…Baseline BCVA was the only significant predictor for BCVA changes among previously treated subjects in a multivariable regression analysis. Several recent studies have stated that most of the missing followup visits in the COVID19 period belonged to the elderly popula tion [28,29]; however, we showed no significant age dif ference between 2020 and 2019. Better baseline BCVA is a known predictor for final BCVA, and in a lower baseline BCVA, a bigger improvement can be achieved [11,30], and we showed among study cohorts that any previous BCVA, within the second year of treatment forward, is a significant BCVA predictor for the following year.…”
Section: Discussioncontrasting
confidence: 83%
“…After ocular manifestations related to COVID-19 were reported, studies have focused on finding out whether the hypercoagulable state caused by COVID-19 can cause retinal vascular abnormality, with RVO and RAO being the most common 16 . However, although many case reports and series have reported suspected RVOs and RAOs caused by COVID-19 based on temporal relationships, the evidence for a definite correlation is yet to be found 7 15 , 17 . Some reports that led to the conclusion of COVID-19 as a cause or at least as a factor leading to retinal vascular complications were cases with no typical risk factors, such as old age or comorbidities, including DM or hypertension, and some bilateral cases 7 , 10 , 11 , 13 , 14 , 18 .…”
Section: Discussionmentioning
confidence: 97%
“…Although the fluorescein angiography revealed some area of peripheral vasculitis, the blood test was negative for any autoimmune disease markers, and no other prothrombotic conditions were found. According to Sharma et al, the reported cases related to vascular occlusion in COVID-19 infection should be associated with deranged coagulation and inflammatory parameters in the absence of confounding factors [9].…”
Section: Discussionmentioning
confidence: 98%